An eco-sustainable parametric design process of bio-based polymers temporary structures - Cecilia Mazzoli; Davide Prati; Marta Bonci (Tema, 2021)
The primary common goal of any resource processing intervention is environmental sustainability. It seeks practical collaboration in construction technology and innovation, whether intentionally used to increase eco-friendly energy savings or implicitly used to reduce the impact of construction projects on the global environment. Biopolymers are a promising field for growth because they combine high technological potential with environmental sustainability. A viable alternative to conventional, costly, and complicated construction systems is the employment of technologies that exploit environmental sustainability concepts to create temporary modular structures that maximize manufacturing times and costs. The paper presents an innovative process for designing temporary structures for social, cultural, and exhibition use. The present paper aims at the following objectives: (i) to illustrate a parametric approach to the design of spaces for such proposes; (ii) to study a prefabricated construction system consisting of interlocking elements to be dry assembled; (iii) to propose the use of new bio-based material. The building system originated based on these research instances targets the requirements of: adaptability, flexibility, and reversibility of spaces; prefabrication, lightness, and speed of installation and assembly; environmental sustainability and recyclability of components employed. In particular, the modules that make up the final product, characterized by vaults, are conceived as small shelters for reading and social activities.